Trends of and implications for the diffusion of lesson study: thematic analysis of WALS2019 conference presentations - Fang, Yanping; Wang, Hongyan (International journal for lesson and learning studies, 2021)
PurposeA first post-WALS attempt at a thematic analysis of the conference presentations since its first annual meeting in 2007, this paper aims to achieve two major purposes: first, to capture the trends of spread and diffusion of lesson and learning studies globally and second, to draw useful implications for future conferences.Design/methodology/approachA thematic analysis using NVIVO12.0 coding on all forms of conference presentations found in the WALS 2019 Conference Programme was conducted. Representative cases were selected from paper and symposiums sessions to support the claims generated from the analysis.FindingsThe study provides an evidence-based confirmation of the global spread and diffusion of lesson and learning studies. It uncovers findings key to the initial spread and continued diffusion; examines funding as a mechanism enabling university–school research relationships, models of adaptations and issues of sustainability; surfaces the theoretical models and methods adopted in paper and symposia presentations. The current situation, lessons learned and possible implications for future WALS conferences are discussed.Research limitations/implicationsInform research on practical cases.Practical implicationsLessons learned are discussed.Social implicationsThese are possible implications for future WALS conferences.Originality/valueThe originality lies in its being the first WALS post-conference analysis aiming at identifying substantive themes with potential to draw important implications for future research and subsequent years' conferences.